ncRNAs mediated RPS6KA2 inhibits ovarian cancer proliferation via p38/MAPK signaling pathway - Fu, Zhiqin; Ding, Chao; Gong, Wangang; Lu, Chao (Frontiers in Oncology, 2023)
Background: Ovarian cancer is the most lethal gynecology malignancy in the world, therefore, research on the molecular biological mechanism of ovarian cancer tumorigenesis and progression has received widespread attention. Methods: We identified RPS6KA2 as the prognosis-related gene of ovarian cancer from TCGA, GSE26712 and GSE26193 database via bioinformatic analysis. qRT-PCR and western blot detected the differential expression of RPS6KA2 in normal ovaries and ovarian cancer tissues. The biological functions of RPS6KA2 were verified by in vitro and in vivo. GSEA analysis was used to select candidate signaling pathway of RPS6KA2 which was further verified by western blot. The possible binding sites of RPS6KA2 with miRNAs and circRNAs were predicted by bioinformatics analysis, and then a circRNA-miRNA-mRNA interaction network was constructed. Results: We found the expression of RPS6KA2 was down-regulated in ovarian cancer tissues. Overexpression of RPS6KA2 could suppress cell proliferation, whereas knockdown of RPS6KA2 had the opposite effects on proliferation. GSEA analysis showed that the MARK signaling pathway was closely associated with RPS6KA2. Bioinformatics analysis and dual-luciferase reporter assay showed that RPS6KA2 was regulated with miR-19a-3p, miR-106a-5p and miR-519d-3p. Further analysis showed that circFAM169A was the common ceRNA of miR-19a-3p, miR-106a-5p and miR-519d-3p. Dual-luciferase reporter assay showed the relationship of circFAM169A and miR-106a-5p and miR-519d-3p. After network analysis, one circRNA-miRNA-mRNA axis (circFAM169A/miR-106a-5p, miR-519d-3p/ RPS6KA2) was identified. Conclusions: We demonstrated that circFAM169A/miR-106a-5p, miR-519d-3p mediated low expression of RPS6KA2 could affect the proliferation of ovarian cancer cells via p38/MAPK signaling pathway.